Why are patients still in hospital after fast-track, unilateral unicompartmental knee arthroplasty - Jensen, Christian Bredgaard; Troelsen, Anders; Nielsen, Christian Skovgaard; Otte, Niels Kristian Stahl; Husted, Henrik; Gromov, Kirill (Acta Orthopaedica, 2020)
Background and purpose — Previous studies have investigated risk factors related to prolonged length of stay following total knee arthroplasty (TKA), but little is known about specific factors resulting in continued hospitalization within the 1st postoperative days after unicompartmental knee arthroplasty (UKA). We investigated what specific factors prevent patients from being discharged on the day of surgery (DOS) and the first postoperative day (POD-1) following primary UKA in a fast-track setting. Patients and methods — We prospectively collected data on 100 consecutive and unselected medial UKA patients operated from December 2017 to May 2019. All patients were operated in a standardized fast-track setup with functional discharge criteria continuously evaluated from DOS and until discharge. Results — Median length of stay for the entire cohort was 1 day. 22% and 78% of all patients were discharged on DOS and POD-1, respectively. Lack of mobilization and pain separately delayed discharge in respectively 78% and 24% of patients on DOS. The main reasons for lack of mobilization were motor blockade (37%) and logistical factors (26%). For patients placed 1st or 2nd on the operating list, we estimate that the same-day discharge rate would increase to 55% and 40% respectively, assuming that pain and mobilization were successfully managed. Interpretation — One-fifth of unselected UKA patients operated in a standardized fast-track setup were discharged on DOS. Pain and lack of mobilization were the major reasons for continued hospitalization within the initial postoperative 24–48 hours. Strategies aimed at decreasing length of stay after UKA should strive to improve analgesia and postoperative mobilization.